2018
DOI: 10.1016/j.jnma.2018.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Diversity in the Clinical and Translational Research Workforce

Abstract: The positive impact of diversity in increasing the effectiveness of the research workforce has been undeniably demonstrated to be an essential element for achieving health equity. Diversity is also instrumental for the research workforce to advance discovery, eliminate health disparities, improve minority health and achieve effective patient-centered outcomes in the quest for better health. One of the sustainable ways to achieve diversity in the workforce is through training, education and career development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 9 publications
0
30
0
Order By: Relevance
“…As mentioned above, results highlight a strong scientific collaboration among PRCTRC affiliated investigators as shown by the high average CC of 0.82 and the high average DC of 0.991 that were found in our results. This could be explained by the multidisciplinary nature of the PRCTRC and of clinical and translational science [17][18][19][20]. The research areas of the PRCTRC publications evaluated in this study covered clinical and basic medical research, including the PRCTRC focus areas of HIV/AIDS, neuroscience, cardiovascular and metabolic disease, and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, results highlight a strong scientific collaboration among PRCTRC affiliated investigators as shown by the high average CC of 0.82 and the high average DC of 0.991 that were found in our results. This could be explained by the multidisciplinary nature of the PRCTRC and of clinical and translational science [17][18][19][20]. The research areas of the PRCTRC publications evaluated in this study covered clinical and basic medical research, including the PRCTRC focus areas of HIV/AIDS, neuroscience, cardiovascular and metabolic disease, and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Both institutions have leveraged CRECD support to extend career development opportunities for junior investigators. A total of 97 MSc graduates from the UPR-MSC CRECD submitted 104 grants; 77 (74%) were funded at approximately $19.1 million, including three R01 awards [ 17 ]. The NIGMS funded National Research Mentoring Network (NRMN) aims to increase R-series grant success of underrepresented scientists [ 12 , 13 ].…”
Section: Appendix A1 Xavier University Of Louisiana (Xula)mentioning
confidence: 99%
“…Both institutions have leveraged CRECD support to extend career development opportunities for junior investigators. A total of 97 MSc graduates from the UPR-MSC CRECD submitted 104 grants; 77 (74%) were funded at approximately $19.1 million, including three R01 awards [ 17 ].…”
Section: Appendix A1 Xavier University Of Louisiana (Xula)mentioning
confidence: 99%
“…We have categorized these into two types of programs: Conference-based [21][22][23] and Institute-based. [24][25][26][27][28][29] Positive features of conference-based mentorship programs were availability of mentors/networks, employing national organizations (ie, National Hispanic Science Network, Society for Advancement of Chicanos/ Hispanics & Native Americans in Science), as a major recruitment source and virtual mentorship network. This provided a valuable resource to offer research-professional networking of inadequate acculturation into the scientific enterprise and also to overcome the lack of local expertise of most institutions to support mentorship of Latino investigators.…”
Section: Section III Latino Mentorship Programsmentioning
confidence: 99%